Cloning, characterization and activity analysis of human choline kinase promoters - See Too, Wei Cun (Pusat Pengajian Sains Perubatan, 2013)
Choline kinase (CK) is the first enzyme in the COP-choline pathway, a de novo biosynthetic pathway for major phospholipid in the membrane of eukaryotic cells i.e phosphatidylcholine (Lykidis et a/., 2001 ). This enzyme catalyzes the phosphorylation of choline by ATP to form phosphocholine. In mammalian cells, choline kinase exists as three isoforms that are encoded by two separate genes named cka and ck/3. ck/3 codes for a single protein (CKJ3) while cka undergoes alternative splicing to produce CKu1 and CKu2 isoforms (Malito eta/., 2006). Increased activity of CK and its product, phosphocholine, have been implicated in human carcinogenesis. Elevated phosphocholine level is a common feature in cell lines derived from human tumors and this parameter seems to be able to distinguish malignant cell lines from normal cell lines irrespective of their proliferation rates (Bhakoo eta/., 1996; Aboagye and Bhujwalla, 1999). Overexpression of CK has been reported in a variety of human cancers such as lung, colo rectal as well as prostate adenocarcinomas (Nakagami et a/., 1999, Ramirez de Molina eta/., 2002a, Ramirez de Molina eta/., 2002b). In addition, studies had demonstrated the increased of CK activity upon induction of the H-ras oncogene in mouse fibroblast cell lines. Inhibition of CK has been proposed to be a potential antitumor strategy (Rodriguez-Gonzalez eta/., 2004). Rodriguez-Gonzalez et al. (2004) demonstrated that CK inhibitors could become potent antitumor drugs both in vitro and in vivo. Recently, CKu protein levels have been found to be drastically increased in both human tumors and cell lines derived from human tumor, when compared to normal tissues or appropriate human primary cells, respectively (Aoyama et a/., 2004). Increased levels of CKu mRNA but not CKJ3 in tumor-derived cell lines was also reported (Gallego-Ortega eta/., 2009).